2018
DOI: 10.1093/trstmh/try065
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of leptospirosis and differentiation in blood parameters between positive and negative cases in dogs of Kathmandu Valley

Abstract: Detection of Leptospira antibody in non-vaccinated dogs indicates a significant threat to human population and demand unique strategic action plan for the control and prevention of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Several studies have reported variable prevalence in dogs ranging from 1.8% in Australia to 71.1% in India (Davis et al., 2008; Zwijnenberg et al., 2008; Shi et al., 2012; Ambily et al., 2013; Bier et al., 2013; Ojha et al., 2018). In Europe, the prevalence ranges from 6% in Ireland to 49% in Italy (Scanziani et al., 2002; Burriel et al., 2003; Schuller et al., 2015b; Llewellyn et al., 2016; Habus et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported variable prevalence in dogs ranging from 1.8% in Australia to 71.1% in India (Davis et al., 2008; Zwijnenberg et al., 2008; Shi et al., 2012; Ambily et al., 2013; Bier et al., 2013; Ojha et al., 2018). In Europe, the prevalence ranges from 6% in Ireland to 49% in Italy (Scanziani et al., 2002; Burriel et al., 2003; Schuller et al., 2015b; Llewellyn et al., 2016; Habus et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 70 dog's blood sample collected from Kathmandu at 2016, on serological analysis 9 sample i.e. 11.4% was positive for Leptospira (KC et al, 2018). In serological analysis of 200 infertile animals ( 114cows and 86 buffaloes), 8.5% animals (11% cows and 5.5% buffaloes) were positive for Leptospirahardo (Joshi, 2000).…”
Section: Leptospirosismentioning
confidence: 99%
“…Важливим для вивчення особливо небезпечних зоонозів лишається клініко-діагностична інформативність, адже закордонні дослідники виявляли антитіла до лептоспірозу у невакцинованих собак, це створює значну загрозу для людства (Ojha et al, 2018), тому наукові пошуки щодо більш глибокого розуміння патогенезу лептоспірозу у собак є актуальним і необхідним. У зв'язку з цим метою наших досліджень було встановити можливість оцінки ендогенної інтоксикації у собак за лептоспірозу на основі показників лейкоцитарних індексів їх крові.…”
Section: вступunclassified
“…Підвищення кількості паличкоядерних на фоні зниження сегментоядерних нейтрофілів (зсув лейкоцитарної формули вліво) характеризує запальний процес з розвитком інтоксикації організму. Сегментоядерні нейтрофіли виконують важливу роль у процесі придушення активності бактерій за рахунок вмісту спеціальних білків, що володіють властивостями антибіотиків, тому зниження їх кількості викликає занепокоєння та передбачає корекцію етіотропної терапії (Ojha et al, 2018;Kim et al, 2019;Radzykhovsʹkyy et al, 2019). Достовірне підвищення кількості еозинофілів (P  0,05) притаманно для розвитку алергічного стану.…”
Section: таблицяunclassified